The spectrum of long-term cognitive and functional outcome after hemispherectomy in childhood. (May 2016) - van Schooneveld, Monique M.J.; Braun, Kees P.J.; van Rijen, Peter C.; van Nieuwenhuizen, Onno; Jennekens-Schinkel, Aag
Abstract: Purpose: To evaluate cognition, behavior, daily functioning and health-related quality of life (HrQoL) five years to more than a decade after hemispherectomy (HE) in childhood. Methods: This countrywide Dutch cohort study of 31 patients, who underwent HE between 1994 and 2009, included a semi-structured interview with parents, an assessment of cognition, and screening of behavioral problems and HrQoL. Results: Twenty-two school-age children and young adults [median age 13.8 years (0.5 at epilepsy onset, 5.3 at HE)] were assessed with age-appropriate cognitive tests. IQ ranged from 45 to 82 (median 61). Despite performing below mean norm scores, these participants could learn and remember, sustain attention, inhibit irrelevant responses, read and write. Nine more children [median age 9.7 years (0.25 at epilepsy onset, 1.4 at HE)] were so mentally retarded that age-appropriate testing was impossible. This group was almost totally dependent on others in daily activities, had the highest proportion of pre-existing contralateral MRI-abnormalities and after HE the highest rates of seizure recurrence and behavioral problems. Parents in both groups rated HrQoL surprisingly positively (mean VAS-score 72.5), with a scarce low rating (40). All parents reported problems with respect to their children's self-care, daily activities and mobility. Conclusion: At least five years after HE, cognitive, behavioral and daily functioning encompasses a broad spectrum that varies from profound retardation and almost total dependence to low normal cognition and a reasonably independent existence. Pre-existing contralateral MRI abnormalities reflect a more generally affected brain with a limited ability to mediate development after HE. Highlights: At least five years after HE in childhood. Cognitive, behavioral and daily functioning encompasses a broad spectrum. Contralateral MRI abnormalities reflect a more generally affected brain with a limited ability to mediate development. Despite remaining physical and cognitive impairments, a rewarding life can be attained.